2020
DOI: 10.1101/2020.02.07.938811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The use of nanovibration to discover specific and potent bioactive metabolites that stimulate osteogenic differentiation in mesenchymal stem cells

Abstract: Figure 2. Metabolic profiles of MSCs in 3D culture for 7 days with osteogenic media or nanovibration. (a) Heatmap (red = up-regulations, blue = down-regulations)and (b) principle component analysis depicting differences in nanovibration and OGM metabolic profiles during MSC differentiation. Metabolic profiles of MSCs induced by nanovibrational stimulation show a greater similarity to unstimulated controls at day 7 of culture and to OGM-stimulated cells at day 14. (c) Metabolic profiles were compared by Ingenui… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Furthermore, the genes involved in osteogenic differentiation of BMSCs were determined by real-time quantitative polymerase chain reaction (RT-qPCR). The relative mRNA of osteogenic gene markers including alkaline phosphatase (ALP), bone morphogenetic protein-2 (BMP-2), runt-related transcription factor 2 (RUNX-2), and osteocalcin (OCN) were selected as representative examples 39,40 . According to Fig.…”
Section: In Vitro Osteogenic Differentiation Promotion By Hydrogelmentioning
confidence: 99%
“…Furthermore, the genes involved in osteogenic differentiation of BMSCs were determined by real-time quantitative polymerase chain reaction (RT-qPCR). The relative mRNA of osteogenic gene markers including alkaline phosphatase (ALP), bone morphogenetic protein-2 (BMP-2), runt-related transcription factor 2 (RUNX-2), and osteocalcin (OCN) were selected as representative examples 39,40 . According to Fig.…”
Section: In Vitro Osteogenic Differentiation Promotion By Hydrogelmentioning
confidence: 99%
“…As discussed, bioactive metabolites are emerging as powerful signalling molecules that can drive cell processes (23, 73), as previously demonstrated in the control of stem cell differentiation (24,74,75). However, their role in cancer dormancy is not understood.…”
Section: Discussionmentioning
confidence: 74%
“…Metabolites can both act as bioactive compounds and fuel biological processes and, as such, are a growing focus of research (23,24,(73)(74)(75). We therefore assessed whether the pQ-EV metabolite cargo could cause a metabolic shift in MCF7 spheroids towards dormancy.…”
Section: Pq-ev Cargo Metabolites Can Influence Mcf7 Spheroid Activity...mentioning
confidence: 99%
“…An interesting new strategy to induce osteogenesis utilizes a nanovibrational bioreactor which delivers ultra-precise vibrations to MSCs for guiding their differentiation into bone cells [16,67,68]. We have shown that stimulating cells with vibrations in the form of nano-meter amplitude results in elevated expression of osteogenic biomarkers such as osteocalcin, osteopontin, alkaline phosphatase and BMP-2.…”
Section: Controlled Growth Factor Release and Nanovibrations For Oste...mentioning
confidence: 99%